2012
DOI: 10.1021/cm301173j
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Orientation in Sputtered TiO2 Thin Films and Its Effect on the Photo-Oxidation of Acetaldehyde

Abstract: Crystal orientation is not typically considered when investigating the reactivity of thin films. We propose that accounting for the preferred crystallographic orientation may serve as an indirect measure of the active sites along the solid− solid interface that are difficult to measure with direct techniques. The goal of this work is to identify the preferred orientation, examine its evolution as a function of synthesis parameters, and determine its effect on photoreactivity. We examine the effect of substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Owing to different surface energies along different plane or orientations [26], the properties and stability of a thin film depend upon the degree of preferred orientation [25]. Therefore, the study of preferred orientation factor is needed.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to different surface energies along different plane or orientations [26], the properties and stability of a thin film depend upon the degree of preferred orientation [25]. Therefore, the study of preferred orientation factor is needed.…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 photocatalytic activity may depend on several parameters; the crystal orientation, for instance, has been reported to have a marked effect, as it can influence the process of electron‐hole separation through surface arrangement . In particular it was shown that crystallite alignment of the (004) orthogonal to the film surface favors a higher reactivity rate …”
Section: Introductionmentioning
confidence: 99%
“…There are much fewer studies on sputter deposited TiO 2 films. It has been reported that sputtered TiO 2 films on biased substrates alter the texturing and preferred orientation depending on bias voltage, leading to an improved photodegradation rate of acetaldehyde as a function of increasing orientation [24]. Other reports show that changing total pressure [25], and O 2 partial pressure [26] may also affect film growth and preferential orientation of anatase films.…”
Section: Introductionmentioning
confidence: 99%